2012
DOI: 10.1002/smll.201101866
|View full text |Cite
|
Sign up to set email alerts
|

Porous Protein Crystals as Reaction Vessels for Controlling Magnetic Properties of Nanoparticles

Abstract: Magnetic bimetallic CoPt nanoparticles are synthesized in the solvent channels of hen egg white lysozyme crystals by the reduction of Co(2+) and Pt(2+) ions pre-organized on the interior surface of the solvent channels. By using different lysozyme crystal systems, the magnetic properties of CoPt nanoparticles can be controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 51 publications
3
70
0
Order By: Relevance
“…As can be seen, the crystalline structures can be easily exposed and isolated with the applied selective etching technique, and their tunable surface structures allow the loading and controllable release of a variety of guest molecules. With the crystalline morphology and surface properties precisely manipulated, combined with the excellent thermal and mechanical properties of the base polymer, the as‐prepared polymeric structures may pursue niche advanced applications in fillers, carriers, adsorbents, and so on 38–40…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, the crystalline structures can be easily exposed and isolated with the applied selective etching technique, and their tunable surface structures allow the loading and controllable release of a variety of guest molecules. With the crystalline morphology and surface properties precisely manipulated, combined with the excellent thermal and mechanical properties of the base polymer, the as‐prepared polymeric structures may pursue niche advanced applications in fillers, carriers, adsorbents, and so on 38–40…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that AuNPs@Lys could be successfully used as biocatalysts with superior performance. For examples, Abe et al 87 prepared bimetallic CoPt nanoparticles with different magnetic properties in the inner surface of the CLLC pores by soaking, washing, chemically reducing of Co 2+ and Pt 2+ , along with other treatments. Furthermore, these researchers also demonstrated that the AuNPs@CLLCs and AgNPs@CLLCs can be used as recyclable catalysts in the reduction of 4-nitrophenol to 4-aminophenol.…”
Section: Applications Of Clpcsmentioning
confidence: 99%
“…A similar method was extended to the preparation of inorganic materials in crystals of hen egg white lysozyme (HEWL) 11. 13, 14 Crystals of HEWL have several important advantages; 1) they can be routinely obtained in quantities exceeding several hundred milligrams overnight, 2) various metal ions and metal complexes can be accumulated in solvent channels of the crystals, and 3) HEWL can be crystallized in tetragonal, orthorhombic, and monoclinic lattices by varying the crystallization conditions (Figure 3).…”
Section: Preparation Of Inorganic Materialsmentioning
confidence: 99%
“…Magnetic properties of bimetallic CoPt nanoparticles (CoPt‐NPs) were regulated by the different environments provided by the individual HEWL crystal systems (Figure 3 a). 11 The crystal structure of the tetragonal HEWL obtained in the presence of Pt 2+ ions shows that five Pt 2+ ions are located in the vicinity of Cys6, Arg14, His15, Ser24, and Asn65. In contrast, the crystal structure of the orthorhombic HEWL in the presence of Pt 2+ ions has five binding sites for Pt 2+ ions in the vicinity of Lys1, Cys6, His15, and Asp119 11.…”
Section: Preparation Of Inorganic Materialsmentioning
confidence: 99%